Primary presentation and clinical course of pediatric and adolescent patients with differentiated thyroid carcinoma after radioiodine therapy - Burgard, Caroline; Zacherl, Mathias Johannes; Todica, Andrei; Hornung, Julia; Grawe, Freba; Pekrul, Isabell; Zimmermann, Petra; Schmid-Tannwald, Christine; Ladurner, Roland; Krenz, Detlef; Trupka, Arnold; Wagner, Johanna; et al. (Frontiers in Oncology, 2023)
Introduction Differentiated thyroid carcinoma (DTC) in childhood and during adolescence is extremely rare. Pediatric DTC commonly presents with advanced disease at diagnosis including high prevalence of cervical lymph node metastases and pulmonary metastases. Studies in children with DTC are limited. Therefore, we aimed to evaluate initial presentation, effectiveness of radioiodine therapy (RIT), and long-term outcome of prepubertal in comparison to pubertal / postpubertal patients. Methods Eighty-five pediatric and young patients aged 6.4 to 21.9 years with histopathologically confirmed DTC were retrospectively included. They all underwent total thyroidectomy followed by RIT. Initial presentation and outcome of prepubertal and pubertal/postpubertal patients were compared one year after RIT, during follow-up, and at the last visit of follow-up. Results Prepubertal patients presented with significantly higher T and M stages. One year after RIT 42/81 (52%) patients still presented with evidence of disease (ED). During follow-up of median 7.9 years, prepubertal patients were less often in complete remission (58% versus 82% in pubertal patients). At the last visit of follow up 19/80 (24%) patients still had ED without statistical differences between the two groups (42% prepubertal vs. 18% pubertal/postpubertal, p-value 0.06). None of our patients died disease-related over the observed period. Conclusion Prepubertal children with DTC presented with a more advanced tumor stage at initial presentation. During follow-up they present more often with ED. However, at the end of our study, we did not observe statistically relevant differences in patient outcome between the prepubertal and pubertal/postpubertal group.